Aspects to be considered to integrate the learning outcomes approach into university curricular design (Innovaciones Educativas, 2021)
The purpose of this article is to present the findings of the research conducted to identify important aspects that should be considered when using the learning outcomes approach in the university curriculum. The research design was qualitative and exploratory, since it was the first approach to the topic. The method used was literature review and interviews with experts in the field. Throughout the article, topics related with this approach such as writing, coherence of learning outcomes in relation to curricular components, use of taxonomies for the classification of knowledge levels, curricular mapping, benefits and challenges are addressed. As main results, it is found that the approach is known at both national and international level and that there are educational proposals that already have it, specifically, the profile, methodology and evaluation. However, at the level of curricular realization in subjects or courses, the efforts are isolated and there is a lack of further treatment of the topic. On the other hand, it is evident that it is essential to have a taxonomy for the writing of learning outcomes, being Bloom's, revised Bloom's and SOLO the most used.
Keywords: Learning; Higher Education; Assessment; Curriculum; Taxonomy; Education